Modulation of biochemical and physiological parameters in Hordeum vulgare L. seedlings under the influence of benzyl-butyl phthalate - Kumari, Arpna; Kaur, Rajinder (PeerJ, 2019)
Background Phthalates are man-made chemical compounds with numerous applications especially known for their use as plasticizers. They have weak bonding to the polymeric matrix or products in which they are used. Owing to this reason, they are readily released into the environment which makes them ubiquitous. The agricultural soils are also reported to be polluted with phthalates up to a considerable extent which causes adverse effects on flora and fauna. A few studies have been conducted on phthalate-induced phytotoxicity, which has revealed that phthalates affect the quality and yield of edible plants. In the last decades, some crops were analyzed for phthalate-induced adversities; among them, barley was the least explored. Methods The present study has investigated the impact of benzyl-butyl phthalate (BBP) on barley (Hordeum vulgare L.) seedlings to address the biochemical, physiological consequences, and toxicological implications. After the exogenous exposure of BBP (viz. 0, 25, 50, 100, 200, 400, 800, 1,600 mg/L) for 7 days, barley seedlings were analyzed for different indices. Results The exposure of BBP mediated a significant (p ≤ 0.05, 0.01) overall elevation in the contents of pigment, proline, soluble protein, carbohydrate, hydrogen peroxide (H2O2), and malondialdehyde (MDA) in shoots and roots of barley seedlings. The activities of superoxide dismutase (SOD), guaiacol peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), and glutathione reductase (GR) were also stimulated significantly in shoots and roots of seedlings against BBP stress except for SOD activity which declined in the roots. The polyphenols (non-enzymatic antioxidants) content was also altered in all the treated concentrations as compared to the control. Furthermore, BBP caused stomatal abnormalities, induced cytotoxicity, and loss of plasma membrane integrity. Conclusions BBP disturbed the normal physiology of barley which could also affect the yield of the crop under field conditions.
Keywords: Benzyl-butyl phthalate; Biochemical responses; Polyphenols profiling; Confocal microscopy; Scanning electron microscopy